2014
DOI: 10.1136/bcr-2013-202089
|View full text |Cite
|
Sign up to set email alerts
|

Corpus cavernosum abscess after Winter procedure performance

Abstract: SUMMARYA 23-year-old male patient with sickle-cell disease reported his third episode of priapism complicated by the presence of a corpus cavernosum abscess after the performance of a Winter procedure 20 days prior to his presentation. While in hospital for 11 days, two penile needle aspirations and three surgical drainages were performed with associated antibiotic therapy. He evolved with erectile dysfunction refractory to drug therapy and his infectious condition improved. An early penile prosthesis implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…During the period of indwelling of the catheter after the operation, we paid attention to the care of the external orifice of the urethra to reduce the occurrence of catheterrelated infections. Although it was reported that patients who received open surgical drainage are more likely to have complications, including poor erectile function, impaired sexual activity, and secondary fibrosis, 6,14,18,19 this patient recovered well from surgery and had a normal erectile function and appearance of the penis, which may be related to a good nursing concept.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…During the period of indwelling of the catheter after the operation, we paid attention to the care of the external orifice of the urethra to reduce the occurrence of catheterrelated infections. Although it was reported that patients who received open surgical drainage are more likely to have complications, including poor erectile function, impaired sexual activity, and secondary fibrosis, 6,14,18,19 this patient recovered well from surgery and had a normal erectile function and appearance of the penis, which may be related to a good nursing concept.…”
Section: Discussionmentioning
confidence: 77%
“…3,[5][6][7][8] If the patients experience severe postoperative erectile dysfunction, they need to be further treated with penile prosthesis implantation. 13,14 Some patients with recurrent penile abscess or pain may have to undergo penectomy. [15][16][17] In the present case, not only was the patient treated with puncture drainage, but also the abscess wall was removed and then the gap was closed layer by layer with primary suture.…”
Section: Discussionmentioning
confidence: 99%
“…Penile abscess with corpus cavernosum involvement is a rare entity whose etiology is still uncertain. Many authors have reported several causal factors, associating it with untreated penile fracture [1][2][3][4][5][6][7], the use of intracavernous therapy for erectile dysfunction [8][9][10][11][12], hematogenous spread after periodontal abscess [13][14][15], perianal [16][17][18], or intracavitary abscess [19], or after drainage or surgical treatment of priapism [20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Other cases presented with priapism by mimetic effect to ischemic priapism [6,21,26]. Few patients presented with purulent urethral discharge at the initial presentation [5,16,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…An abscess in the corpus cavernosum is a rare clinical entity. It has been reported in the context of infectious diseases and is sometimes preceded by penile trauma (1)(2)(3). However, it has rarely been described in the context of non-infectious diseases, and whether or not a cavernosal abscess can be non-infectious remains unclear.…”
Section: Introductionmentioning
confidence: 99%